ANALISIS TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA PENGGUNAAN SISTEM INFORMASI KEPEGAWAIAN (SIKEP) DI PTTUN SURABAYA - Nathania, Widya; Sri Wulandari, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sistem Informasi Kepegawaian (SIKEP) is a web-based application that all employees at the Pengadilan Tinggi Tata Usaha Negara (PTTUN) of Surabaya are required to use to support personnel administration. The mandatory nature of this system raises concerns regarding employee acceptance of the technology, given that actual usage does not fully reflect users' free choice, compounded by technical issues such as delayed data synchronization and instability of the centralized system. This study aims to analyze the effect of perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention to use on the actual system use of SIKEP at PTTUN Surabaya, both partially and simultaneously, using the Technology Acceptance Model (TAM) approach. This research employed a quantitative approach with an explanatory design. The population and sample consisted of 56 SIKEP user employees, selected using a census technique. Primary data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 27. Actual system use was measured based on respondents' perceptions rather than system log data, as the researcher had no personal access to the SIKEP application. The results show that perceived usefulness and attitude toward using have a positive but not significant effect on actual system use, while perceived ease of use and behavioral intention to use have a positive and significant effect. Simultaneously, all four variables significantly affect actual system use, contributing 87.9%. These findings indicate that ease of use and intention to use are the dominant factors in SIKEP acceptance, while the system's mandatory nature weakens the influence of perceived usefulness and attitude on actual usage.